Recent Publications (Quarterly Journal of Economics, 1959)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 73, Issue 2, May 1959, Pages 348–350, https://doi.org/10.1093/qje/73.2.348 Published: 01 May 1959